2018
DOI: 10.1016/j.sjbs.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of fresh Barhi dates for quality preservation during frozen storage

Abstract: Fresh harvested dates are perishable and there is a need for extending their shelf life while preserving their fresh like quality characteristics. This study evaluates three different freezing methods, namely cryogenic freezing (CF) using liquid nitrogen; individual quick freezing (IQF) and conventional slow freezing (CSF) in preserving the quality and stability of dates during frozen storage. Fresh dates were frozen utilizing the three methods. The produced frozen dates were frozen stored for nine months. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 24 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…The results showed that the stage of maturity (at different harvesting time) significantly ( p ≤ .05) influenced all studied physical properties. The data are comparable to Alhamdan, Hassan, Alkahtani, Abdelkarim, and Younis () work with slight variations. Those variations conceivably might be attributed to the age of palm trees, location, and harvesting operations.…”
Section: Resultssupporting
confidence: 88%
“…The results showed that the stage of maturity (at different harvesting time) significantly ( p ≤ .05) influenced all studied physical properties. The data are comparable to Alhamdan, Hassan, Alkahtani, Abdelkarim, and Younis () work with slight variations. Those variations conceivably might be attributed to the age of palm trees, location, and harvesting operations.…”
Section: Resultssupporting
confidence: 88%
“…The reduction in hardness, elasticity, and chewiness, during ripening may be due to breakdown of insoluble solids into soluble solids or by cellular breakdown leading to membrane porousness. Equivalent results of the efficacy of GA 3 in preserving fruit texture are stated by other authors for different fruits [9,11,[33][34][35][36] . Preservation of fruit texture by SA pretreatment has been identified earlier in several fruits [37,38] .…”
Section: Textural Parametersmentioning
confidence: 88%
“…Fruit samples were compressed with a rod velocity of 1.5 mm/s to a depth of 5 mm. The obtained force-time deformation curves were used to calculate the following textural parameters: hardness, elasticity and chewiness [11] .…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to extend the permissible period of storage and marketing of perishable foodstuffs, a number of conservation methods and techniques can be applied [1][2][3][4][5][6]: preservation by using low temperatures (refrigeration, freezing, modified atmosphere); preservation by using high temperatures (pasteurization, sterilization); conservation by reducing the water content of the product (dehydration, concentration); preservation by the use of inhibitors of depreciation phenomena (natural antimicrobials, bacteriocins, sugar addition, acidification, chemical preservatives etc. ); preservation by unconventional methods (ionizing radiation, high pressure, high voltage electrical impulses, non-ionizing radiation, ozone, ultrasound, photodynamics, etc.).…”
Section: Introductionmentioning
confidence: 99%